Designing and the construction of traditional and innovative 3D printed radiotherapy mask - Yiap, Lee Kien (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
Perspex or thermoplastic devices are moulded directly to patient anatomy especially for immobilization when patients undergoing brain or head and neck radiotherapy. Some studies found that direct moulding can be distressing for patient and the shells do not always fit perfectly. A treatment shell able to generate directly from three dimensional (3D) printer with the help from a computer. This paper focuses on improving the flexibility and quality of the existing treatment shell. The innovative custom made treatment shell was then designed and printed by using 3D printer. To segment the surface of the patient's head from CT or MRI datasets, computer algorithms were used. After segmentation, 3D model which is suitable for printing on 3D printer is constructed. The material used to construct the prototypes were acrylonitrile butadiene stryrene Innovative custom made treatment shells allow end users to choose any shape to cover any region depends on patient’s condition such as swallowing on cheek. The flexibility of the treatment shells were increased gives good impact to treatment deliver.